FRI0008 Longitudinal Analysis of the IGH-VH Gene by High-Throughput Sequencing in Early Rheumatoid Arthritis Paired Biopsies and its Association with Response to Dmards. (9th June 2015) - Carlotti, E.; Floyd, J.; Murray-Brown, W.; Barnes, M.; Mehr, R.; Bombardieri, M.; Pitzalis, C.
Abstract : Background: B cells play a multi-faceted role in the pathogenesis of rheumatoid arthritis (RA) by producing autoantibodies, acting as antigen presenting cells and propagating the inflammatory environment by releasing cytokines and chemoattractant molecules. 1 Objectives: To test the hypothesis that synovial B cell clones may escape therapy and repopulate the synovium, we investigated the heavy chain of the immunoglobulin gene (IgH) in paired biopsies, from pre- and post- methotrexate treated RA patients, using a high-throughput sequencing approach. Methods: The IgH-VH gene repertoire was analysed in 8 RA samples (4 patients) collected from the same joint before and 6 months after treatment with methotrexate. Two of the patients were responder and 2 non-responder (NR), according to the DAS28 >1.2 criteria. Total RNA was retro-transcribed with mu, gamma, alpha isotype specific primers and the whole cDNA used for 36 PCR amplifications, performed with 12 VH forward and 3 isotype reverse primers. 2 In total 177 amplicons, across 8 samples (from RA1 to RA8) were generated and sequenced on a Roche GS-FLX Titanium platform. Results: We generated ∼90, 000 reads (range RA2, 3979 – RA6, 15426) of >350 bases across the 8 libraries. The 2 samples that according to immunohistochemistry had the lowest level of infiltrating B cells showed the lowest number of reads. The majority of sequences belonged to the isotype gamma (52.5%), followed by mu (30.4%) and alpha (17.1%). We observed diversity across the different libraries in terms of VH and JH gene usage and isotype prevalence. In total we identified 1546 different clonotypes (defined as reads that use the same VH and JH genes and have the same CDR3 length). Clonotypes expressing the VH1-69 gene, which are preferentially used by rheumatoid factor B cells, were significantly reduced in number after treatment. Conversely, no difference was observed in the usage of the autoreactive VH4-34 gene, in the CDR3 length, presence of charged amino acids in the CDR3 loop, number of somatic hypermutations or replacement/silent mutations. Interestingly, after comparison of identical clonotypes in paired biopsies, in 1 NR patient we detected 6 clonotypes that persisted 6 months after DMARDs; lineage tree analysis showed that the clones detected in the second biopsy were more differentiated and displayed a higher number of SHM and/or a switched isotype. Conclusions: This pilot study confirmed the ability of high-throughput sequencing technologies to capture B cell diversity at great depth, allowing us to perform studies of clonal evolution on a large scale. We observed a high diversity across the different samples and in 1 NR case we detected 6 clones that survived treatment and displayed features of proliferation and/or differentiation. Future studies performed on larger cohorts and on biopsies from patients treated with Rituximab will address the important unknown question of whether repopulation within the joint occurs from escaped synovial clones or from re-emerging novel auto-reactive clones from the bone marrow. References: Corsiero E. et al, Drug Discov Today. 2014 Aug;19(8):1161-5 Tiller, T., et al. J Immunol Methods 329, 112-124 (2008). Disclosure of Interest: None declared